The Potential Socio-Economic Impact of China Pakistan Economic Corridor - Ali, Liaqat; Mi, Jianing; Shah, Mussawar; Shah, Sayed Jamal; khan, Salim; BiBi, Kausar (Asian Development Policy Review, 2017)
Road and transport corridor play a significant role in the development of the country. This study examines the socio economic impact of China Pakistan Economic Corridor. Pakistan and China has great relations from the beginning. China Pakistan economic corridor is very significant for both countries as it provide access of China to the warm water of Arabian Sea through a short and safe route which will save billions of shipping charges and time and will cover the current energy crises in Pakistan and provide employment and trade opportunities for the local people which will minimize unemployment and poverty in Pakistan and will improve the living standard and boost the economy of Pakistan.